Evaluasi Keserasian Kerja Alat Gali Muat dan Alat Angkut Guna Pencapaian Target Produksi Batugamping 350.000 ton/bulan pada Pit 242 Bukit Karang Putih PT Semen Padang (Persero) di Kecamatan Lubuk Kilangan Sumatera Barat - M.Arief Adilah; E.P.S.B Taman Tono; Delita Ega Andini (MINERAL, 2019)
The tendency of increasing demand for limestone as one of the raw materials for making cement, it is necessary to have appropriate mining to fulfill these needs. The importance of synchronization of loading and hauling equipments in working optimally and efficiently will influences the ability of mechanical devices in productivity. Match factors can find out the comparison of the number of loading and hauling equipment working in mining operations. Analysis of the calculation of match factors based on the circulating time of mechanical devices and the number of devices operating, data taken 30 times a month in July 2018. The primary data such as; circulation time of mechanical devices, resistance factors, bucket and vessel real capacity, effective working time of devices and number of devices, while secondary data such as; devices specifications, devices and operator work time, layout maps, rainfall and company production targets. The research method used is the calculation and analysis of quantitative data on factors that influence the ability of mechanical devices in production. The production target for limestone mining in pit 242 is 350,000 tons / month using a Hitachi ex 2500-6 Excavator unit synchronized with five units of Dumptruck Komatsu HD 785-7. Current devices production capability is 262,198.66 tons / month with a value factor of 0.80. The problem that occurs is not yet achieved the planned production target, this is due to the still low effective working time and work efficiency as a result of existing constraints. Efforts to increase production can be done by improving the effective working time of initially 637.99 minutes per day to 707.30 minutes per day or 81.29% of the total available working time, adding the number of bulk filling to 6 times and adding transportation equipment as many as two units, so that production increased to 361,415.82 tons per month and the value of the match factor for mechanical devices increased to 0.96.